Integration of Renewable Energy Power Plants on a Large Scale and Flexible Demand in Bangladesh's Electric Grid-A Case Study - Halim, Md Abdul; Akter, Mst. Sumi; Biswas, Shuvankar; Rahman, Md. Shahriar (Control Systems and Optimization Letters, 2023)
The fundamental objective of this article is to put in renewable energy sources strategically within the context of Bangladesh's electric infrastructure. Solar and wind energy are inherently intermittent and variable, depending on weather conditions. Because of this unpredictability, power generation can fluctuate, making it difficult to maintain a consistent and reliable energy supply. The case study focuses on the problems and opportunities given by large-scale renewable energy power plant integration and the construction of a flexible demand system. The study digs into the technical, economic, and environmental elements of this integration, taking into account factors like as grid stability, fluctuation in energy supply, and the possibility for lowering greenhouse gas emissions. The abstract shows the potential benefits of such integration for Bangladesh's energy landscape and provides useful insights into the broader subject of renewable energy integration in poor countries through a thorough examination. This study can help future recommendations by policy-makers, producers, entrepreneurs, and utilities grow to enable for large-scale renewable energy penetration into the primary utility grid of a community by providing an outline of the energy supply difficulties in Bangladesh considering techno-economic advantages.